Ownership structure and voting on antitakeover amendments - Brickley, James A.; Lease, Ronald C.; Smith, Clifford W. (Journal of Financial Economics, 1988)
Theory suggests that shareholders who own blocks of stock have a stronger incentive to invest in voting on corporate issues than nonblockholders. Our evidence indicates that institutional investors and other blockholders vote more actively on antitakeover amendments than nonblockholders, and opposition by institutions is greater when the proposal appears to harm shareholders. Our evidence suggests that institutions that are less subject to management influence, such as mutual funds, foundations, and public-employee pension funds, are more likely to oppose management than banks, insurance companies, and trusts, which frequently derive benefits from lines of business under management control.